CLINICAL AND MORPHOLOGICAL CLASSIFICATION OF CEREBRAL INTRAVENTRICULAR HEMORRHAGES - V. V. Vlasyuk ("Paediatrician" Publishers LLC, 2013)
Inconsistency of the current classification of cerebral intraventricular hemorrhages is discussed in the article. The author explains divergence of including of the subependymal (1st stage) and intracerebral (4th stage) hemorrhages into this classification. A new classification of cerebral intraventricular hemorrhages including their origin, phases and stages is offered. The most common origin of intraventricular hemorrhages is subependymal hemorrhage (82,2%). Two phases of hemorrhage were distinguished: bleeding phase and resorption phase. Stages of intraventricular hemorrhages reflecting the blood movement after the onset of bleeding are the following: 1 - infill of the up to ½ of the lateral ventricles without their enlargement; 2 - infill of more than ½ of the lateral ventricles with their enlargement; 3 - infill of the IV ventricle, of the cerebellomedullary cistern and its dislocation into the subarachnoid space of the cerebellum, pons varolii, medulla oblongata and spinal cord.